Evaluación petrolera y métodos de explotación en la Cuenca de Chicontepec - Vázquez Morín, Ángel (My University, 2015)
Evaluación petrolera y métodos de explotación en la Cuenca de Chicontepec
Evaluación petrolera y métodos de explotación en la Cuenca de Chicontepec
Keywords: Evaluación petrolera y métodos de explotación en la Cuenca de Chicontepec